Design and Demonstration of a Passive Pitch System for Tidal Turbines (Proceedings of the European Wave and Tidal Energy Conference, 2023)
Tidal currents are renewable and predictable energy sources that could prove fundamental to the transition to a sustainable use of renewable energy resources. Over a tidal period, changes in the flow speed in a tidal channel require that the blade pitch is adjusted to maximise power extraction. This is currently achieved with active pitch actuation, which however increases the capital and maintenance cost of the turbine. Furthermore, because of turbulence in the tidal stream, turbine yaw, wave-induced currents, etc., tidal turbine blades experience high-frequency velocity fluctuations that result in power and thrust unsteadiness, both of which are transmitted to the generator, the tower, and the active pitching mechanism, shortening the operating life due to fatigue loading.A passive morphing blade concept capable of reducing the load fluctuations without affecting the mean loads has recently been formulated and demonstrated with low-order simulations (https://doi.org/10.1016/j.renene.2021.10.085) and measurements (https://doi.org/10.1016/j.renene.2023.01.051). The system allows both passive pitch adjustment to changes in the mean flow speed over the tidal period, and the mitigation of high-frequency fluctuations.In this paper, we present the recent progress on the development of morphing blade technology, including with numerical simulations and experimental tests on a 1.2-m diameter turbine. Two different design concepts have been tested in the FloWave facility at the University of Edinburgh and in the recirculating channel at the Institute for Marine Engineering of the Italian National Research Council, respectively.Experimental results show that the amplitude of power variations over a wide range of flow speeds is substantially decreased, while thrust variations with changes in freestream speed are essentially suppressed. The detrimental effect of yawed inflow is, in addition, almost entirely cancelled. The fluctuations in the root-bending moment, thrust and torque are consistently reduced over a broad range of tip-speed ratios. We also show that such a system, if improperly designed, could result in a negative starting torque, and we show the steps necessary to avoid this issue.Furthermore, we present a theoretical and numerical framework that allows the design of passive pitch blades that can cancel either thrust or power fluctuations in specific flow conditions, as well as mitigating both types of fluctuations over a wide range of conditions. Specifically, we show that for any quasi-steady change in the relative flow speed and direction, there is a pitching axis that allows a chosen force component to be kept constant. High-frequency force fluctuations can also be substantially mitigated, and the extent of the mitigation depends on the inertia and friction in the system.Overall this paper demonstrates experimentally the effectiveness of morphing blades for tidal turbines and presents a theoretical and numerical framework for the future development of this technology.